Inflammatory Cytokines and BDNF Response to High-Intensity Intermittent Exercise: Effect the Exercise Volume - Cabral-Santos, Carolina; Castrillón, Carlos I. M.; Miranda, Rodolfo A. T.; Monteiro, Paula A.; Inoue, Daniela S.; Campos, Eduardo Z.; Hofmann, Peter; Lira, Fábio S. (Frontiers in Physiology, 2016)
The purpose of this study was to compare the effects of two similar high-intensity intermittent exercises (HIIE) but different volume 1.25km (HIIE1.25) and 2.5km (HIIE2.5) on inflammatory and BDNF responses. Ten physically active male subjects (age 25.22±1.74years, body mass 78.98±7.31kg, height 1.78±0.06m, VO2peak 59.94±9.38ml•kg•min-1) performed an incremental treadmill exercise test and randomly completed two sessions of HIIE on a treadmill (1:1 min at vVO2max with passive recovery). Blood samples were collected at rest, immediately and 60-minutes after the exercise sessions. Serum was analyzed for glucose, lactate, IL-6, IL-10 and BDNF levels. Blood lactate concentrations was higher immediately post-exercise compared to rest (HIIE1.25: 1.69±0.26 to 7.78±2.09mmol•L-1, and HIIE2.5: 1.89±0.26 to 7.38±2.57mmol•L-1, p<0.0001). Glucose concentrations did not present changes under the different conditions, however, levels were higher 60-min post-exercise than at rest only in the HIIE1.25 condition (rest: 76.80±11.14 to 97.84±24.87mg•dL-1, p<0.05). BDNF level increased immediately after exercise in both protocols (HIIE1.25: 9.71±306 to 17.86±8.59ng.mL-1, and HIIE2.5: 11.83±5.82 to 22.84±10.30ng.mL-1). Although both exercises increased IL-6, level percent increase between rest and immediately after exercise was higher in the HIIE2.5 than HIIE1.25 (30% and 10%; p=0.014, respectively). Moreover, IL-10 levels percent increase between immediately and 60-min post-exercise was higher in HIIE2.5 than HIIE1.25 (37% and 10%; p=0.012, respectively). In conclusion, both HIIE protocols with the same intensity were effective to increase BDNF and IL-6 levels immediately after exercise while only IL-10 response was related to the durantion of exercise indicanting the importance ofthis exercise prescription variable.